Uruguay : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Uruguay. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2017 Article IV Consultation highlights that the fiscal adjustment in Uruguay is on track. Fiscal policy has been countercyclical in 2017, with higher income tax receipts partly offset by rising pension and health care costs. The overall deficit is estimated to decline to 3.3 percent of GDP, and the government continues to be able to access international financial markets on favorable terms, including through global nominal-peso bonds. Financial flows have remained volatile, and local and nonresident investor interest in the peso has been strong overall. The current account balance has been improving and is now in surplus, estimated to approach 2 percent of GDP in 2017.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet